Let $ f$ be a function such that $ f\in C_{2\pi}^{0}(\mathbb{R},\mathbb{R}) $ (f is $2\pi$-periodic) such that $ \forall x \in [0,\pi]$: $$f(x)=x(\pi-x)$$

Computing the Fourier series of $f$ and using Parseval's identity, I have computed $\zeta(2)$ and $\zeta(4)$.

How can I compute $ \zeta(6) $ now?

Fourier series of $ f $:

$$ S(f)= \frac{\pi^2}{6}-\sum_{n=1}^{\infty} \frac{\cos(2nx)}{n^2}$$

$$ x=0, \zeta(2)=\pi^2/6$$

  • 2
    $\begingroup$ What did you find for the Fourier series? $\endgroup$ – Davide Giraudo Mar 3 '12 at 15:34
  • 1
    $\begingroup$ Generally for $\zeta(6)$ you will need to do the Fourier series for some polynomial of higher degree. $\endgroup$ – GEdgar Mar 3 '12 at 17:01
  • 1
    $\begingroup$ Replace $f$ with $f_0 = f - \bar{f}$, where $\bar{f}$ is the mean of $f$ over the interval in question. This is again a quadratic function and the Fourier series can be obtained from that of $f$. Now let $F_0$ be a periodic antiderivative of $f_0$. Its Fourier series can be obtained by integrating $S(f)$ and therefore will have coefficients like $n^{-3}$. Parseval's Theorem should allow you to arrive at $\zeta(6)$. $\endgroup$ – Hans Engler Apr 5 '12 at 12:08
  • 1
    $\begingroup$ The following MSE link shows a standard technique that can be used to find $\zeta(6).$ $\endgroup$ – Marko Riedel Feb 19 '14 at 23:29

One method is to consider the generating function of $\zeta(2k)$: $$ \begin{align} f(x) &=\sum_{k=1}^\infty\zeta(2k)\,x^{2k}\\ &=\sum_{k=1}^\infty\sum_{n=1}^\infty\frac{x^{2k}}{n^{2k}}\\ &=\sum_{n=1}^\infty\frac{x^2/n^2}{1-x^2/n^2}\\ &=\sum_{n=1}^\infty\frac{x^2}{n^2-x^2}\\ &=-\frac{x}{2}\sum_{n=1}^\infty\left(\frac{1}{x-n}+\frac{1}{x+n}\right)\\ &=-\frac{x}{2}\left(\pi\cot(\pi x)-\frac1x\right)\\ &=\frac12(1-\pi x\cot(\pi x))\tag{1} \end{align} $$ In light of equation $(1)$, find the power series of $$ x\cot(x)=\sum_{k=0}^\infty a_kx^{2k} $$ $$ \cos(x)=\frac{\sin(x)}{x}\sum_{k=0}^\infty a_kx^{2k} $$ $$ \begin{align} \sum_{n=0}^\infty(-1)^n\!\frac{x^{2n}}{(2n)!} &=\sum_{n=0}^\infty(-1)^n\!\frac{x^{2n}}{(2n+1)!}\;\;\sum_{k=0}^\infty a_kx^{2k}\\ &=\sum_{n=0}^\infty\left(\sum_{k=0}^n(-1)^k\!\frac{a_{n-k}}{(2k+1)!}\right)x^{2n}\tag{2} \end{align} $$ Comparing the coefficients of the powers of $x$ in $(2)$ yields $$ \begin{align} a_n &=\frac{(-1)^n}{(2n)!}-\sum_{k=1}^n(-1)^k\!\frac{a_{n-k}}{(2k+1)!}\\ &=\frac{(-1)^n2n}{(2n+1)!}-\sum_{k=1}^{n-1}(-1)^k\!\frac{a_{n-k}}{(2k+1)!}\tag{3} \end{align} $$ Since $a_n=-2\dfrac{\zeta(2n)}{\pi^{2n}}$ for positive $n$, $(3)$ becomes $$ \zeta(2n)=\frac{(-1)^{n-1}\pi^{2n}}{(2n+1)!}n+\sum_{k=1}^{n-1}\!\frac{(-1)^{k-1}\pi^{2k}}{(2k+1)!}\zeta(2n-2k)\tag{4} $$ Equation $(4)$ gives $\zeta(2n)$ recursively for positive $n$: $$ \begin{align} \zeta(2)&=\frac{\pi^2}{3!}=\frac{\pi^2}{6}\\ \zeta(4)&=-\frac{\pi^4}{5!}2+\frac{\pi^2}{3!}\zeta(2)=\frac{\pi^4}{90}\\ \zeta(6)&=\frac{\pi^6}{7!}3-\frac{\pi^4}{5!}\zeta(2)+\frac{\pi^2}{3!}\zeta(4)=\frac{\pi^6}{945}\\ \zeta(8)&=-\frac{\pi^8}{9!}4+\frac{\pi^6}{7!}\zeta(2)-\frac{\pi^4}{5!}\zeta(4)+\frac{\pi^2}{3!}\zeta(6)=\frac{\pi^8}{9450} \end{align} $$


I have posted here in Portuguese a recursive method based on the computation of the Fourier trigonometric series expansion for the function defined in $\left[ -\pi ,\pi \right] $ by $f(x)=x^{2p}$ and extended to all of ${\mathbb R}$ periodically with period $2\pi.$ This is a shorter description than the original. In this reply I outline the case $\zeta(4)$. For $p=3$ the expansion is

$$x^{6}=\dfrac{\pi ^{6}}{7}+2\displaystyle\sum_{n\ge 1}^{}\left( \left( \dfrac{6}{n^{2}}\pi ^{4}-\dfrac{120}{n^{4}}\pi ^{2}+\dfrac{720 }{n^{6}}\right)\cos n\pi \right) \cos nx.\tag{1}$$

The computation is as follows:

$$\begin{equation*} f(x)=x^{2p}=\frac{a_{0,2p}}{2}+\sum_{n=1}^{\infty }\left( a_{n,2p}\cos nx+b_{n,2p}\sin nx\right) , \end{equation*}$$ where the coefficients are given by the following integrals $$\begin{eqnarray*} a_{0,2p} &=&\frac{1}{\pi }\int_{-\pi }^{\pi }x^{2p}\;\mathrm{d}x=\frac{2\pi ^{2p}}{2p+1}, \\ a_{n,2p} &=&\frac{1}{\pi }\int_{-\pi }^{\pi }x^{2p}\cos nx\;\mathrm{d}x=\frac{2}{\pi } \int_{0}^{\pi }x^{2p}\cos nx\;\mathrm{d}x, \\ b_{n,2p} &=&\frac{1}{\pi }\int_{-\pi }^{\pi }x^{2p}\sin nx\;\mathrm{d}x=0. \end{eqnarray*}$$ The series expansion is thus $$\begin{equation*} x^{2p}=\frac{\pi ^{2p}}{2p+1}+\frac{2}{\pi }\sum_{n=1}^{\infty }\cos nx\int_{0}^{\pi }x^{2p}\cos nx\;\mathrm{d}x.\tag{2} \end{equation*}$$ For $f(\pi )=\pi ^{2p}$ we obtain $$ \begin{equation*} \pi ^{2p}=\frac{\pi ^{2p}}{2p+1}+\frac{2}{\pi }\sum_{n=1}^{\infty }\cos n\pi \int_{0}^{\pi }x^{2p}\cos nx\;\mathrm{d}x, \end{equation*}$$ where the integral $$ \begin{equation*} I_{n,2p}:=\int_{0}^{\pi }x^{2p}\cos nx\;\mathrm{d}x \end{equation*}$$ satisfies the following recurrence, as can be shown by integration by parts $$\begin{equation*} I_{n,2p}=\frac{2p}{n^{2}}\pi ^{2p-1}\cos n\pi -\frac{2p(2p-1)}{n^{2}} I_{n,2\left( p-1\right) },\qquad I_{n,0}=0.\tag{3} \end{equation*}$$

  • For $p=1$, we get $$\begin{equation*} I_{n,2}=\frac{2p}{n^{2}}\pi ^{2p-1}\cos n\pi. \end{equation*}$$ and $$\begin{eqnarray*} \pi ^{2} &=&\frac{\pi ^{2}}{3}+\frac{2}{\pi }\sum_{n=1}^{\infty }\cos n\pi \cdot I_{n,2} \\ &=&\frac{\pi ^{2}}{3}+\frac{2}{\pi }\sum_{n=1}^{\infty }\cos n\pi \left( \frac{2}{n^{2}}\pi \cos n\pi \right) \\ &=&\frac{\pi ^{2}}{3}+4\sum_{n=1}^{\infty }\frac{1}{n^{2}} \\ &\Rightarrow &\zeta (2)=\sum_{n=1}^{\infty }\frac{1}{n^{2}}=\frac{\pi ^{2}}{6 } \end{eqnarray*}$$
  • For $p=2$, we get $$ \begin{equation*} I_{n,4}=\left( \frac{4\pi ^{3}}{n^{2}}-\frac{24\pi }{n^{4}}\right) \cos n\pi \end{equation*}$$ and $$ \begin{eqnarray*} \pi ^{4} &=&\frac{\pi ^{4}}{5}+\frac{2}{\pi }\sum_{n=1}^{\infty }\cos n\pi \cdot I_{n,4}=\frac{\pi ^{4}}{5}+\frac{4\pi ^{4}}{3}-48\sum_{n=1}^{\infty } \frac{1}{n^{4}} \\ &\Rightarrow &\zeta (4)=\sum_{n=1}^{\infty }\frac{1}{n^{4}}=\frac{\pi ^{4}}{ 90}. \end{eqnarray*}$$
  • Finally for $p=3$, we get $$\begin{equation*} I_{n,6}=\left( \frac{6\pi ^{5}}{n^{2}}-\frac{120\pi ^{3}}{n^{4}}+\frac{720}{ n^{6}}\right) \cos n\pi \end{equation*}$$ and $$ \begin{equation*} \pi ^{6}=\frac{\pi ^{6}}{7}+2\sum_{n=1}^{\infty }\left( \frac{6\pi ^{4}}{ n^{2}}-\frac{120\pi ^{2}}{n^{4}}+\frac{720}{n^{6}}\right), \end{equation*}$$ from which the result follows $$\zeta(6)= \begin{equation*} \sum_{n=1}^{\infty }\frac{1}{n^{6}}=\frac{\pi ^{6}}{945}. \end{equation*}$$

Plots of the periodic function defined in $\left[ -\pi ,\pi \right] $ by $f(x)=x^{6}$ (blue curve) and of the partial sum with the first 10 terms of its Fourier trigonometric series (red curve).

enter image description here

This method generates recursively the sequence $(\zeta(2p))_{p\ge 1}$.

  • 1
    $\begingroup$ I think you have a typo: $\pi^6/945$, not $\pi^4/945$. $\endgroup$ – alex.jordan Mar 3 '12 at 23:45
  • 1
    $\begingroup$ @alex.jordan: Thanks! Fixed. $\endgroup$ – Américo Tavares Mar 3 '12 at 23:48
  • 3
    $\begingroup$ Thank you for both your answers! $\endgroup$ – Chon Mar 4 '12 at 17:22
  • 1
    $\begingroup$ @Chon: You are welcome! $\endgroup$ – Américo Tavares Mar 5 '12 at 14:32

You may start with (for $x \in [0,1]$)
$$B_1(x)=x-\frac 12=2\sum_{n=1}^{\infty} \frac{(-1)^n}{2\pi n}\sin\left(2\pi n\left(x-\frac 12\right)\right)$$

and integrate multiple times $x-\frac 12$ (adding the necessary constant when required!) to get :

$$B_{2k}(x)=2(-1)^k\sum_{n=1}^{\infty} \frac{(-1)^n}{(2\pi n)^{2k}}\cos\left(2\pi n\left(x-\frac 12\right)\right)$$ (this is detailed in this paper page 6)

You could too use following formula $$ \cot(\pi z)=\frac1{\pi}\left[\frac1{z}-\sum_{k=1}^{\infty}\frac{2z}{k^2-z^2}\right] $$ (obtained from computation of Fourier series of $\cos(zx)$ for $-\pi \le x \le \pi$ with the result :

$$ \cos(zx)=\frac{2z\sin(\pi z)}{\pi}\left[\frac1{2z^2}+\frac{\cos(1x)}{1^2-z^2}-\frac{\cos(2x)}{2^2-z^2}+\frac{\cos(3x)}{3^2-z^2}-\cdots\right] $$ applied to $x=\pi$)

and deduce an interesting expansion of $\frac z2\left(\cot\left(\frac z2\right)\right)$ in powers of $z^2$.

  • 1
    $\begingroup$ Thank you for your help! $\endgroup$ – Chon Mar 3 '12 at 22:09

Let $f(t):=t^3\ \ (-\pi\leq t\leq \pi)$, extended to all of ${\mathbb R}$ periodically with period $2\pi$. The Fourier series of this function is $$t^3=\sum_{k=1}^\infty {2(-1)^{k-1}(k^2\pi^2-6)\over k^3}\sin(kt)\qquad(-\pi\leq t\leq \pi).$$ We now use Parseval's formula $$\|f\|^2=\sum_{k=0}^\infty |c_k|^2.$$ But $$\|f\|^2={1\over\pi}\int_{-\pi}^\pi x^6\>dt={2\pi^6\over7}$$ and
$$c_k^2={4(k^2\pi^2-6)^2\over k^6}=4\left(\frac{36}{k^6}-\frac{12\pi^2}{k^4}+\frac{\pi^4}{k^2}\right),k\geq1.$$ Noting that $$ \sum_{k=1}^\infty \frac{12\pi^2}{k^4}=12\pi^2\frac{\pi^4}{90}=\frac{2\pi^6}{15}, \sum_{k=1}^\infty\frac{\pi^4}{k^2}=\pi^4\frac{\pi^2}{6}=\frac{\pi^6}{6}$$ we have $$ \sum_{k=1}^\infty \frac{1}{k^6}=\left({\pi^6\over14}+\frac{2\pi^2}{15}-\frac{\pi^4}{6}\right)/36=\frac{\pi^6}{945}. $$


Let $$g(x) = \sum_{n=1}^{\infty} \frac{\cos(2nx)}{n^2}$$


$$g^3(x)=\sum_{n=1}^{\infty}\sum_{m=1}^{\infty}\sum_{k=1}^{\infty} \frac{\cos(2nx)\cos(2mx)\cos(2kx)}{n^2m^2k^2}$$

Since $\cos(a)\cos(b)=\frac{1}{2}\left(\cos(a+b)+\cos(a-b)\right)$ then

$$g^3(x)=\frac{1}{2}\sum_{n=1}^{\infty}\sum_{m=1}^{\infty}\sum_{k=1}^{\infty} \frac{\cos(2nx)\cos(2mx+2kx)+\cos(2nx)\cos(2mx-2kx)}{n^2m^2k^2}$$

Due to orthogonality of cosine function we get after integration :

$$\int_0^\pi g^3(x)\;\mathrm{d}x=\frac{\pi}{4}\sum_{n=1}^{\infty}\sum_{m=1}^{\infty}\sum_{k=1}^{\infty} \frac{\delta_{n,m+k}+\delta_{n,m-k}}{n^2m^2k^2}= \frac{\pi}{2}\sum_{m=1}^{\infty}\sum_{k=1}^{\infty} \frac{1}{(m+k)^2m^2k^2}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.